2023
DOI: 10.1093/ibd/izad119
|View full text |Cite
|
Sign up to set email alerts
|

Histological Disease Activity as Predictor of Clinical Relapse, Hospitalization, and Surgery in Inflammatory Bowel Disease: Systematic Review and Meta-Analysis

Abstract: Background The clinical impact of histological remission on short- and long-term clinical outcomes in patients with inflammatory bowel disease (IBD) is not well established. We assessed risk of clinical relapse, hospitalization, and need for surgery in patients achieving histological remission in comparison with active histological disease. Methods A systematic review was conducted using MEDLINE, Scopus, Cochrane CENTRAL, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…This underscores the potential benefits of targeting histological healing to optimise treatment strategies for IBD. 88 Despite this, the precise role of histology in IBD management remains unclear. There is an ongoing need to better define and understand the implications of histological remission in the context of IBD.…”
Section: Histologymentioning
confidence: 99%
“…This underscores the potential benefits of targeting histological healing to optimise treatment strategies for IBD. 88 Despite this, the precise role of histology in IBD management remains unclear. There is an ongoing need to better define and understand the implications of histological remission in the context of IBD.…”
Section: Histologymentioning
confidence: 99%
“…In addition, the long-term outcome analysis showed that the risk of needing surgery and hospitalization was significantly higher in patients with active histological disease. 21 These meta-analyses suggest that using histological inflammation as a therapeutic target may improve clinical outcomes even if patients with UC achieved endoscopic remission.…”
Section: Introductionmentioning
confidence: 99%